2003
DOI: 10.3168/jds.s0022-0302(03)73635-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolytic Enzymes and Parity Effects on Feeding Behavior, Salivation, and Ruminal pH of Lactating Dairy Cows

Abstract: Four multiparous and four primiparous lactating dairy cows fitted with ruminal cannulas were used in a duplicated 4 x 4 Latin square design to study the effects of parity and inclusion of a fibrolytic enzyme product (Agribrands International, St. Louis, MO) on feeding and chewing behavior, salivation, and ruminal pH. Diets consisting of rolled barley, barley silage, and alfalfa haylage (55% forage, DM basis) differed in enzyme application: 1) control, 2) enzyme applied to concentrate (45% of TMR), 3) enzyme ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
4
32
2
6
Order By: Relevance
“…Some differences between the present results and findings of BOWMAN et al (2003) may be partially caused by differences in the definition of visit and meal criterion. BOWMAN et al (2003) defined a visit as eating activity greater than 30 s and more than 300 g of feed being removed from the feeder, and also meals within close proximity had to be greater than 10 min apart to be considered separate and distinct meals. By contrast, in the current study, a visit was defined as the time spent by an individual cow with her head in one of the troughs, regardless of how the cow spent that time.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Some differences between the present results and findings of BOWMAN et al (2003) may be partially caused by differences in the definition of visit and meal criterion. BOWMAN et al (2003) defined a visit as eating activity greater than 30 s and more than 300 g of feed being removed from the feeder, and also meals within close proximity had to be greater than 10 min apart to be considered separate and distinct meals. By contrast, in the current study, a visit was defined as the time spent by an individual cow with her head in one of the troughs, regardless of how the cow spent that time.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the number of visits per meal was similar between cows in the 1st and 2nd lactation, there was a significant difference between cows in the 1st lactation and cows in the 3rd-and-more-lactation. BOWMAN et al (2003) found a significant difference in daily time eating (347 vs. 323 min/d) and daily DMI (20.50 vs. 23.00 kg/d) but no difference in the number of meals per day (13.4 vs. 13.5) between primiparous and multiparous cows. Some differences between the present results and findings of BOWMAN et al (2003) may be partially caused by differences in the definition of visit and meal criterion.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations